Closed Basins in the Eastern Lake Van in the Plio-Quaternary; Environment Conditions and Geomorphological Developments - Zorer, Halil; Tonbul, Saadettin (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Lake Van, which is one of the important lakes in the world, is located in Eastern Anatolia. The lake, which is formed geomorphologically by neotectonic processes, is surrounded by the Ihtiyar Sahap Mountains, the eastern extension of the Taurus orogenic belt in the south, and bounded by high volcanic mountains in the north and west. The Van Lake basin, which has no outflow, is a closed basin. The Van Lake Closed Basin, which covers a large area of approximately 12500 km(2), is fed by many large and small streams. However, the lake is mainly fed by three major streams (Bendimahi, Engil and Karasu). These three streams are in the form of bowl-shaped plains. These depressions are connected to the river valleys by grabbing throats. These depressions, which are independently closed basins in the Plio-Quaternary, also differ in terms of their environmental characteristics from the Lake Van closed basin. These closed small basins in the east of Lake Van were captured by the rivers in the Quaternary and joined the Lake Van Basin. Tectonism-related faulting was supported by the grabbing. By investigating the geomorphological developments and environmental characteristics of these depressions, which form the upper ground of the river basins, comparisons were made and the differences were revealed.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Lake Van; Closed Basin; Environment; Grapping; Intermontane Basin